ADULT ATTACHMENT STYLE DAN CELEBRITY WORSHIP PADA WANITA DEWASA AWAL PENGGEMAR DRAMA KOREA - Shinta Tri Dewi; Dewi Retno Suminar (Program Studi Psikologi Universitas Malahayati, 2022)
ABSTRACT: ADULT ATTACHMENT STYLE AND CELEBRITY WORSHIP IN EARLY ADULT WOMAN KOREAN DRAMA FANS This study aims to determine whether there is a relationship between adult attachment style and celebrity worship in early adult women who are fans of Korean dramas. Celebrity Worship is the worship of celebrities that goes beyond parasocial interactions where a person becomes very obsessed with one or more celebrities. Meanwhile, adult attachment is emotional between adult partners. The research subjects were early adult women found 183 people. The measuring instrument used is the Experience in Close Relationship-Revised (ECR-R) to measure the type of adult attachment and the Celebrity Attitude Scale (CAS) to measure celebrity adoration. Data analysis was carried out using Pearson's Product Moment correlation technique. The results of data analysis showed that there was a significant positive relationship between attachment anxiety-ambivalence dimensions and celebrity worship (r(181)= .324; p= .00). This result means that the higher the attachment anxiety-ambivalence, the higher the celebrity worship level and vice versa. Meanwhile, in the avoidant attachment dimension with worship celebrities, there is no significant relationship.Theoretical, practical implications and research limitations are discussed in the discussion section. Keywords: Adult Attachment, Celebrity Worship, K-drama fans Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara adult attachment style dan celebrity worship pada wanita dewasa awal penggemar drama Korea. Celebrity worship adalah pemujaan terhadap selebriti yang melebihi interaksi parasosial dimana seseorang menjadi sangat terobsesi dengan satu atau lebih selebriti. Sedangkan adult attachment adalah ikatan emosional antara pasangan romantis orang dewasa. Subjek penelitian adalah wanita dewasa awal berjumlah 183 orang. Alat ukur yang digunakan adalah Experience in Close Relationship-Revised (ECR-R) untuk mengukur adult attachment style dan Celebrity Attitude Scale (CAS) untuk mengukur celebrity worship. Analisis data dilakukan dengan teknik korelasi Pearson Product Moment. Hasil analisis data menunjukkan bahwa ada hubungan positif yang signifikan antara dimensi anxiety-ambivalent attachment dengan celebrity worship (r(181)= .324; p= .00). Hasil ini bermakna bahwa semakin tinggi anxiety-ambivalent attachment maka akan semakin tinggi pula tingkat celebrity worship dan sebaliknya. Sedangkan pada dimensi avoidant attacment dengan celebrity worship tidak terdapat hubungan yang signifikan. Implikasi teoretis, praktis dan keterbatasan penelitian dibahas di bagian diskusi. Kata Kunci: Adult Attachment, Celebrity Worship, Penggemar K-drama